THE INFLUENCE OF PEER EDUCATION ON ENHANCING PARENTS MOTIVATION IN ACHIEVING BALANCED NUTRITION PROVISION - Rizona, Firnaliza; Citra, Viona Fracellia (Jurnal Keperawatan, 2025)
Nutritional issues among children remain a significant public health concern in Indonesia, as indicated by the high prevalence of stunting and obesity due to suboptimal fulfillment of balanced nutrition. Parental motivation plays a crucial role in ensuring the quality of children's nutritional intake, although it is often influenced by limited knowledge and inadequate support. Peer education is considered an effective strategy to enhance parental motivation by optimizing interactions among parents to share information and experiences related to the implementation of balanced nutrition practices. The purpose of this study was to analyze the effect of peer education on improving parents' motivation to fulfill balanced nutrition for elementary school students. This study was a pre-experimental design. The population consisted of parents of elementary school children in Palembang City, with a total of 20 respondents selected through purposive sampling. The intervention was conducted through peer education sessions facilitated by parents. The results of the statistical test showed a significant increase in parental motivation following the intervention, with a p-value of 0.035. Parents are encouraged to optimize their role in providing balanced dietary intake for their children by maintaining strong motivation as an effort to help prevent nutritional status problems in children.